Position control of permanent magnet DC motor - Aljawabrah, Ayham (Design of Machines and Structures, 2025)
This paper presents a study of a DC motor position control system, a critical component in many industrial applications. A detailed mathematical model is developed to represent the motor's dynamics. Three advanced control strategies, namely Linear Quadratic Regulator (LQR), Linear Quadratic Integral (LQI), and Model Predictive Control (MPC), are designed and implemented to control the motor position. An open-loop simulation is conducted to verify the DC motor model. The performance of these controllers is evaluated and compared through closed-loop step response and closed-loop ramp response scenarios. The comparison is based on several matrices, such as the rise time, settling time, and overshoot. The simulation results showed that the LQR has the fastest response, but the MPC is the most energy efficient.